Perception towards the Policy Implementation Practices in Institutional Performance of Public Enterprises: A Case of Gorkhapatra Corporation - Phuyal, Shreeram; Palikhe, Amin (Kanya Journal, 2025)
The purpose of this article is to examine the perception towards the policy implementation practices in institutional performance of public enterprises with reference to Gorkhapartra Corporation that assess the requirement of the major dimensions of policy implementation practices in institutional performance. This study tries to the possible reform measures regarding effective implementation of major dimensions of policy implementation. An exploratory case research design was adopted with applying thematic analysis. The nine key informant interviews had been taken to suggest the best dimensions of policy implementation practices for enhancing the institutional performance of public enterprises. The study found that partial control is essential with complete autonomy. The public accountability and responsibility are necessary where policy innovation and institutional capacity can minimize the policy implementation. It is essential for better institutional performance. The finding from the key informant interview can be instrumental to the other similar types of governmental enterprises. Therefore, it has managerial, policy level, methodological and theoretical implication, can act as a limelight for future research perspective. The comprehensive study could be done on dimensions of policy implementation practices for institutional performance.